Web Accessibility Web Standards and Regulatory Compliance - Rutter, Richard; Lauke, Patrick H.; Waddell, Cynthia; Thatcher, Jim; Lawton Henry, Shawn; Lawson, Bruce; Kirkpatrick, Andrew; Heilmann, Christian; Burks, Michael R.; Regan, Bob; Urban, Mark (Apress : Imprint: Apress, 2006)
The power of the Web lies in the fact that anyone and everyone can access it, and this should also extend to users with disabilities. Accessibility is about making websites accessible to those with aural, visual, or physical disabilities, or rather, constructing websites that don't exclude these people from accessing the content or services provided. This isn't difficult to accomplish and doesn't require anything more than your normal tool set-HTML, CSS, JavaScript, Flash, or whatever else. All you need to do is use these tools in the right way, and bear in mind the guidelines that exist to help you keep your websites accessible and the laws that enforce web accessibility around the world. This book gives you all you need to know about web accessibility, whether you are a web designer or developer who wants your sites to be accessible, or a business manager who wants to learn the impact of web accessibility laws on your websites. After an overview of the accessibility law and guidelines, and a discussion about accessibility and its implementation in the enterprise, the book goes on to show how to implement accessible websites using a combination of concise references and easy-to-follow examples, covering: Understanding assistive technologies Creating accessible content using XHTML, JavaScript, CSS, Flash, and PDFs Testing against WCAG (including 2.0) and Section 508 Retrofitting inaccessible sites where necessary The book concludes with an in-depth analysis of accessibility law around the world. If you're concerned about the legal and moral implications of web accessibility, then this book is perfect for you. It is written by some of the world's experts on accessibility, leaving you in good hands.